Constraints on anomalous Higgs boson couplings using production and decay information in the four-lepton final state - (:unkn) unknown (ELSEVIER, 2017)
A search is performed for anomalous interactions of the recently discovered Higgs boson using matrix element techniques with the information from its decay to four leptons and from associated Higgs boson production with two quark jets in either vector boson fusion or associated production with a vector boson. The data were recorded by the CMS experiment at the LHC at a center-of-mass energy of 13 TeV and correspond to an integrated luminosity of 38.6 fb(-1). They are combined with the data collected at center-of-mass energies of 7 and 8 TeV, corresponding to integrated luminosities of 5.1 and 19.7 fb(-1), respectively. All observations are consistent with the expectations for the standard model Higgs boson. (C) 2017 The Author. Published by Elsevier B.V.
Keywords: Higgs; Exotic spin; Anomalous coupling; PSEUDO-OBSERVABLES; BROKEN SYMMETRIES; SPIN; MASS